Functional action analysis: a psychological model for the development of a problem-solving competence in game sports. - Magnaguagno, Lukas; Charbonnet, Bryan (International Journal of Sport & Exercise Psychology, 2026)
Coaches are amazed by exceptional player performances in game sports. A psychological concept – problem-solving competence – has gained attention as one explanatory factor for such performances. We present a conceptual analysis of problem-solving competence and introduce a theory-informed, practice-oriented game sports specific model: Functional Action Analysis. Using information-processing perspective as the foundation, our model includes two main phases: (a) understanding the problem constellation and (b) shaping the problem constellation. We break down the two phases into four steps: (1) capturing: directing attention towards relevant cues; (2) recognising: using task-specific prior knowledge; (3) deciding: cultivating if–then automatisms; and (4) executing: consistently implementing intended decisions in motor behaviour. By analysing each step from two standpoints – fundamental understanding and practical utility – we show how our model functions as a valuable tool for the coaching process in game sports. Our model helps analyse and explain successful and unsuccessful actions, pinpointing their respective causes, and provides guidance for designing effective training sessions.